DOI: 10.31274/rtd-180813-13616
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of interactive online instruction in the dietetic internship

Abstract: This is to certify diat the Doctoral dissertation of Ruth Edson Litchfield has met the dissertation requirements of Iowa State University Committee Member Committee Member Committee Member Major Professor For the Major Program Fo^j^l^raduate College Signature was redacted for privacy. Signature was redacted for privacy. Signature was redacted for privacy. Signature was redacted for privacy. Signature was redacted for privacy. Signature was redacted for privacy. Signature was redacted for privacy. iii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(100 reference statements)
1
1
0
Order By: Relevance
“…The results of Slavin's research (1983) indicated that the utilization of cooperative learning methods could affect students' achievement levels significantly, improve friendships across ethnic groups, improve students' self-esteem levels, and positively affect their interactions with academically handicapped students. In addition, the cooperative learning method could empower students' critical thinking skills and ensure active learning (Litchfield, 2000). This study supports the findings of both Slavin and Litchfield.…”
Section: Constructivist and Cooperative Activities Improve Students' supporting
confidence: 84%
“…The results of Slavin's research (1983) indicated that the utilization of cooperative learning methods could affect students' achievement levels significantly, improve friendships across ethnic groups, improve students' self-esteem levels, and positively affect their interactions with academically handicapped students. In addition, the cooperative learning method could empower students' critical thinking skills and ensure active learning (Litchfield, 2000). This study supports the findings of both Slavin and Litchfield.…”
Section: Constructivist and Cooperative Activities Improve Students' supporting
confidence: 84%
“…The levels chosen in this regard were novice, advanced beginners, competent, proficient and expert nursing professionals. Whereas, online skills and relationships, access to technology, motivation, internet discussion, online audio-video ads, and importance of success were taken as sub-categories of e-learning readiness 19 . In this regard, the analysis of the results in the previous section indicated that no big difference is observed between the population mean of the nurses and the sample mean as the p-value for the one-test sample was found to be 0.000, and the results regard- ing the readiness of e-learning among different levels of nursing are true for the whole population.…”
Section: Discussionmentioning
confidence: 99%